2016
DOI: 10.11111/jkana.2016.22.3.230
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Patient Safety Behaviors of Nurses in Inter-Hospital Transfer

Abstract: Purpose:The purpose of this study was to investigate predictors of nurses' patient safety behavior during inter-hospital transfer. The study was based on the Theory of Planned Behavior (TPB). Methods: A descriptive survey design was used. Data were collected with a self-administrated 39-item questionnaire completed by 111 nurses from a university hospital in Seoul, South Korea. The questionnaire was developed based on the Theory of Planned Behavior (TPB) guideline and included measure of self-reported past pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Higher scores indicated emerging adults’ perception that parents, friends, university, and official and non-official sources believed that they should perform preventive behavior. A previous study showed a Cronbach’s alpha coefficient of 0.96 [ 19 ]. The Cronbach’s alpha in this study was 0.76.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher scores indicated emerging adults’ perception that parents, friends, university, and official and non-official sources believed that they should perform preventive behavior. A previous study showed a Cronbach’s alpha coefficient of 0.96 [ 19 ]. The Cronbach’s alpha in this study was 0.76.…”
Section: Methodsmentioning
confidence: 99%
“…Subjective norms are individuals’ behavioral norms or beliefs that are shaped by their social environment such as friends, parents, or significant others; these social-environmental factors act as motivation for conforming to these norms [ 15 ]. Several studies have sought to demonstrate the effect of subjective norms in terms of health behaviors [ 16 , 17 , 18 , 19 ]. Recent evidence suggests that social norms, specifically among friends and family, are likely to lead people to adopt more preventive behaviors and to perform these behaviors more frequently during the COVID-19 pandemic in the USA [ 20 ].…”
Section: Introductionmentioning
confidence: 99%